Why Day 3 biopsy mosaicism is blamed for the lack of success of PGD-A?. (April 2019) - Eibes, P.; Francis, E.; Chaturvedi, R.; Nawaz, M.; Shyju, S.; Thulasidas, D.; Hellani, A.
Abstract : Introduction: Preimplantation Genetic Diagnosis- Aneuploidy Screening (PGD-A) is a technique commonly used in conjunction with IVF treatments. PGD-A is intended to identify those embryos with greater likelihood to implant. It is offered to patients at increased risk of producing chromosomally abnormal embryos (increased maternal age, Recurrent miscarriage, IVF failure and severe male factor). Technical related Error rates of PGD-A have fallen from 7% when using FISH to less than 1% when using modern techniques such as Next Generation Sequencing (NGS). Another source of error that is related to the physiology of the embryos is mosaicism described as the presence of two or more cells lines within an embryo. The advantage of NGS made the detection of mosaicism easier due to the i) higher sensitivity in aneuploidy detection and ii) the reliability of the technique making non-mosaicism related error minimal. The objective of our study is to assess the mosaicism rate and the misdiagnosis rate due to euploid/aneuploid mosaic embryos on day 3 biopsy. Material and Methods: Embryos from patients undergoing PGD-A were biopsied on day 3 and sent to our laboratory for Aneuploidy Screening by NGS. Blind Reanalysis ofembryonic cells from embryos diagnosed as aneuploid but with good morphology and development was performed. Rebiopsy was carried out either on day 4, day 5 or day 6. Both, original analysis and reanalysis were performed by NGS (MySeq, Illumina platform). Result(s): PGD-A was performed in our laboratory on 29309 embryos at cleavage stage from 2016 to date. Rebiopsy for 173 embryos, originally diagnosed as aneuploidy, were blindly reanalyzed. There was 118 out of 173 showed aneuploidy (91.3%) while 15 out of 173 were found euploids (8.7%). The aneuploid embryos were divided into 3 categories: first where 118 embryos out of 173 (68.2%) showed the same initial result; second, 37 of the 173 (21.4%) showed at least one aneuploidy that was present in the initial result and third 3 out 173 (1.7%) showed a different an inverted figure of deletion/duplication for the same chromosome. Conclusions: This study shows a very high confirmation rate (more than 90%) for day 3 biopsies. Our misdiagnosis rate after day 3 biopsy is 8.7%, due to mosaicism. Our data support the usefulness of day 3 biopsy PGD-A by NGS in places where day 5 biopsy is not possible. The mosaic rate on a relatively high number of embryos observed in this study is in line with other similar reported data. Our reanalysis was based on rebiopsies on embryos showing a good division after the first biopsy which might explain the low mosaic rate. Despite the high accuracy in day 3 biopsy diagnosis, implantation/pregnancy rate is still in the range of 50-60% implicating the necessity of finding more embryonic viability markers allowing a better outcome after IVF/PGD-A.